A case of spontaneous mesenteric hematoma with diagnostic difficulty - Nobuhisa Tanioka; Hiromichi Maeda; Sachi Tsuda; Jun Iwabu; Tsutomu Namikawa; Mitsuko Iguchi; Kazuhiro Hanazaki (Surgical Case Reports, 2020)
Abstract Background Spontaneous mesenteric hematoma (SMH) is a rare condition characterized by intraperitoneal hemorrhage of unknown etiology. SMH without worsening of general status allows conservative management; however, patients showing chronological changes on imaging require surgical intervention to rule out possible malignancy. Case presentation A 69-year-old man was referred to our hospital to evaluate an abdominal mass with no associated clinical symptoms. He had a history of chronic hepatitis C and diabetes mellitus. Six months earlier, computed tomography (CT) revealed a 75-mm tumor arising from the jejunum, suspected to be a gastrointestinal stromal tumor (GIST) of the small intestine. Following a further 6 months of observation, the patient was referred to our hospital. Abdominal contrast-enhanced CT revealed a well-defined heterogeneous round tumor with a maximum diameter of 75 mm adjacent to the upper jejunum. The tumor was accompanied by calcification at the periphery, with no evidence of augmentation over the prior 6 months. Diffuse lymphadenopathy was observed around the aorta and splenic artery. Under the diagnosis of GIST arising from small intestine, the patient underwent elective surgery. The resection revealed an elastic soft tumor at the mesentery adjacent to the upper jejunum with severe adhesion between the tumor and jejunum. The tumor origin was unclear; thus, we performed mesenteric excision and partial enterectomy without lymph node dissection. The tumor was surrounded by fibrous capsular tissue containing massive hemosiderin deposits and cholesterol crystals showing partial calcification, resulting in a diagnosis of spontaneous hematoma of the mesentery. Conclusions We report a case of SMH mimicking small intestinal GIST. It is difficult to diagnose long-established SMH because its radiological features change with time, and more case reports are needed to improve the accuracy of diagnosis.